Moral Values and Social Values in the Novel Sawitri dan Tujuh Pohon Kelahiran by Mashdar Zainal as an Effort to Select Learning Materials for Literary Appreciation - Irawan, Dedi; Azhar, Zalfa Nopianda (Jurnal Indonesia Sosial Sains, 2024)
This research is motivated by students’ lack of knowledge about literary works that they deserve to read. This is in line with the teacher’s lack of supervision over the selection of literary appreciation learning materials that are worthy of being read, appreciated, and used in high school. The teacher has an important role in selecting literary appreciation learning materials. Extensive insight into the field of literature, the ability to motivate students to enjoy literature and to make students being interested in appreciating a literary work an ability that must have an Indonesian language teacher. This study aims to describe the moral and social values in the novel Sawitri and the Seven Trees of Birth by Mashdar Zainal, as well as its feasibility as material for studying literary appreciation in high school. The method used in this research is the descriptive qualitative method. Data collection techniques in this study using content analysis techniques. The data source was obtained from the novel Sawitri and the Seven Trees of Birth by Mashdar Zainal. The results obtained from this study are, 1) the moral values contained in the novel Sawitri and the Seven Trees of Birth by Mashdar Zainal include the moral values of human relations with oneself and human relations with others. There are as many as 28 moral values which include moral values of bad attitude in the novel Sawitri and the Seven Trees of Birth by Mashdar Zainal; 2) the social values contained in the novel Sawitri and the Seven Trees of Birth by Mashdar Zainal’s work covers social values among the people in the Sawitri family. There are 11 social values in the Sawitri and the Seven Trees of Birth by Mashdar Zainal. Based on the moral and social values contained in novel Sawitri and the Seven Trees of Birth by Mashdar Zainal deserve to used as learning material for literary appreciation in high school.